The Effects of consuming 6 weeks of beetroot juice (Beta vulgaris L.) on hematological parameters in female soccer players - Lotfi, M.; Azizi, M.; Tahmasbi, W.; Bashiri, P. (Journal of Kermanshah University of Medical Sciences, 2018)
Background: The present study aimed to investigate the effects of consuming 6 weeks of beetroot juice (Beta vulgaris L.) on hematological parameters in female soccer players. Methods: Twenty female soccer players were selected randomly and assigned into two groups: Experimental (beetroot juice, n = 10) and control (placebo, n = 10). Subjects trained for six weeks (three 90-min sessions per week) by consuming 200 mL of juice 2 hours prior to training. Blood samples were collected and investigated (Hb, Hct, RBC, Iron, MCV, Ferritin and TIBC) in pre- and posttest. Paired Sample t-test and Independent Sample t-test were used for comparision within and between groups, respectively. Statistical significance was P<0.05. Results: Results showed that the experimental group had significant increases in the Hb, Hct, RBC, iron, and ferritin levels (P < 0.05). No significant difference was detected in MCV levels (t = -1.10, P = 0.29) and there was a significant decrease in the TIBC (t = 4.99, P = 0.001). In the control group, there were significant differences in (Hct, iron, ferritin and TIBC) (P < 0.05). In addition, there were significant differences in (Hb, Hct, RBC, iron, ferritin and TIBC) levels between experimental and control subjects (P < 0.05), but there was no significant difference in MCV (t = 1.11, P = 0.28). Conclusions: Since beetroot juice consumption has significant effects on the levels of some hematological parameters in female soccer players, it can be used to prevent and improve anemia among these athletes.